2002
DOI: 10.1016/s0893-133x(01)00296-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking Abstinence on Visuospatial Working Memory Function in Schizophrenia

Abstract: Schizophrenic patients have impairments in cognitive function, including deficits in visuospatial working memory (VSWM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
150
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 43 publications
(46 reference statements)
12
150
3
1
Order By: Relevance
“…Enhancement of cholinergic neurotransmission has been shown to improve memory performance by improving the selectivity of perceptual processing during encoding (Furey et al, 2000). Two prior studies have observed improved memory performance in healthy adult smokers during acute smoking abstinence (George et al, 2002;Jacobsen et al, 2004). The present findings suggest that this effect occurs in adolescent smokers and is modified by prenatal exposure to active maternal smoking.…”
Section: Discussionsupporting
confidence: 57%
“…Enhancement of cholinergic neurotransmission has been shown to improve memory performance by improving the selectivity of perceptual processing during encoding (Furey et al, 2000). Two prior studies have observed improved memory performance in healthy adult smokers during acute smoking abstinence (George et al, 2002;Jacobsen et al, 2004). The present findings suggest that this effect occurs in adolescent smokers and is modified by prenatal exposure to active maternal smoking.…”
Section: Discussionsupporting
confidence: 57%
“…Some studies indicate that cigarette smoking or nicotine may ameliorate some of the cognitive deficits in schizophrenic patients (Smith et al, 2002;George et al, 2002;Hahn et al, 2012), suggesting that cigarette smoking or nicotine serves as a form of selfmedication. However, in our present study, we found that smoking was negatively associated with RBANS total score and the Visuospatial/Constructional index in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Avila et al (2003) have reported that nicotine reduces the number of leading (or anticipatory) saccades during smooth pursuit tasks both in people with schizophrenia and in healthy controls. There is also evidence that nicotine maintains visuospatial working memory performance in people with schizophrenia (George et al 2002).…”
Section: Discussionmentioning
confidence: 99%